Two new species of the genus Eotmethis (Orthoptera, Acridoidea, Pamphagidae) from China - Ye, Bao-Hua; Shi, Jian-Ping; Zhi, Yong-Chao (Zootaxa, 2015)
Two new species of the genus Eotmethis Bey-Bienko, 1948, namely Eotmethis xiai sp. nov., and Eotmethis platyverticus sp. nov. from the Ningxia Hui Autonomous Region and Gansu province are described in this paper. The new species Eotmethis xiai sp. nov. is allied to E. recipennis Xi & Zheng, 1986, but differs from latter by the vertical diameter of eye about 1.2 times as long as horizontal diameter, prozona of pronotum equal to metazona, tegmina of female shorter, reaching 2nd abdominal tergite only. The new species Eotmethis platyverticus sp. nov. is allied to E. holanennis Zheng & Gow, 1981, but differs from latter by width of vertex between eyes 2 times diameter of eye and prozona of pronotum longer than metazoan in female. The type specimens are deposited in College of Life Sciences, Hebei University, Baoding, China.